Physical development of young basketball players with different types of posture - Nevolin , D. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. Changes in the physiological curves of the spinal column, joint hypermobility, transverse and longitudinal flat feet, etc. are signs of connective tissue dysplasia, which can lead to significant overload of various parts of the locomotor system in athletes, and thus to injury and diseases of the locomotor system and internal organs of the human body. According to numerous studies, the problems of functional disorders of the locomotor system of children and young people have also not escaped the practice of sports. Experts attribute these disorders to the trends in modern sport, which include intensification of training loads and lowering the age limit at the initial stage of athletes’training. There is evidence that functional disorders of the musculoskeletal system in childhood pose a major health threat if they are not detected in a timely manner and measures are not taken to eliminate them. In such cases, they become the basis for more persistent disorders and diseases of not only the musculoskeletal system, but also internal organs and systems. The purpose of the study is to determine somotometric features of basketball players of 9-10 years old with different types of posture. Research methods:theoretical analysis and synthesis of literary sources; pedagogical observation. To determine the types of posture, the program “Torso”, pedagogical experiment, methods of mathematical statistics were used. The results. The measurements of somatometric indicators obtained in groups of young athletes were analysed in the following ways: a) assessment of the level of expression of each indicator by comparing with the data on norms according to age; b) comparison of data in groups of young basketball players with different types of posture within a certain age category; c) determination of differences between athletes of different ages with the same type of posture. Conclusions. It was shown that the majority of basketball players aged 9 and 10 were above average or tall according to WHO standards, while according to the standards of the Ministry of Health of Ukraine their height corresponded to the average norm. As for the weight of the athletes, most of them complied with the average norm by both standards. It was determined that somatometric characteristics of athletes with different types of posture do not differ. At the same time, significant differences were found between children aged 9 and 10, indicating higher height, higher weight and larger chest volume of older athletes.